Lifetime incidence and age of onset of mental disorders, and 12-month service utilization in primary and secondary care: a Finnish nationwide registry study - Kimmo Suokas; Ripsa Niemi; Mai Gutvilig; John J. McGrath; Kaisla Komulainen; Jaana Suvisaari; Marko Elovainio; Sonja Lumme; Sami Pirkola; Christian Hakulinen (Epidemiology and Psychiatric Sciences)
Abstract Background Previous studies have estimated the lifetime incidence, age of onset and prevalence of mental disorders, but none have used nationwide data covering both primary and secondary care, even though mental disorders are commonly treated in primary care. We aimed to determine lifetime incidence, age-specific incidence, age of onset and service utilization for diagnosed mental disorders.